2021
DOI: 10.36076/ppj.2021.24.e161-e168
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Opioid Consumption After Lumbar Fusion Using Ultrasound-Guided Lumbar Erector Spinae Plane Block: A Randomized Controlled Trial

Abstract: BACKGROUND: The erector spinae plane block (ESPB) is gaining popularity in lumbar fusion for postoperative pain management. OBJECTIVES: The aim of this study was to investigate the changes of opioid consumption after surgery, the range of cold temperature sensory blockade, pain, and safety. STUDY DESIGN: Randomized controlled study. SETTING: Single center. METHODS: Patients who were randomized to ESPB with 0.375% ropivacaine (ropivacaine group) and mock ESPB with saline (saline group) and underwent posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…Of the 15 trials included [ 6 – 8 , 12 23 ], one [ 17 ] involved free-hand ESPB, while the others [ 6 – 8 , 12 16 , 18 23 ] were ultrasound-guided (USG-guided) ESPB. The main local anesthetics used included bupivacaine [ 6 – 8 , 12 14 , 16 , 18 , 19 ], ropivacaine [ 20 23 ], levobupivacaine [ 15 ], and mixtures of bupivacaine and lidocaine [ 17 ]. The features of the included trials are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 15 trials included [ 6 – 8 , 12 23 ], one [ 17 ] involved free-hand ESPB, while the others [ 6 – 8 , 12 16 , 18 23 ] were ultrasound-guided (USG-guided) ESPB. The main local anesthetics used included bupivacaine [ 6 – 8 , 12 14 , 16 , 18 , 19 ], ropivacaine [ 20 23 ], levobupivacaine [ 15 ], and mixtures of bupivacaine and lidocaine [ 17 ]. The features of the included trials are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All trials [ 6 – 8 , 12 23 ] reported postoperative opioid consumption; however, only one trial [ 13 ] reported opioid consumption 8 hours after surgery. The pooled analysis showed that ESPB could reduce 4 to12 hours (SMD = −2.46, 95% CI (−3.62, −1.29); p < 0.01; Figure 3 ), 24 hours (SMD = −2.27, 95% CI (−3.21, −1.32); p < 0.01; Figure 4 ), and 48 hours (SMD = −0.83, 95% CI (−1.05, −0.60); p < 0.01; Figure 5 ) postoperative opioid consumption.…”
Section: Resultsmentioning
confidence: 99%
“…[20] Finally, 19 articles were included in this systematic review and meta-analysis. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The detailed screening process and selection results are shown in Figure 1. The characteristics of the included 19 RCTs enrolling in 1561 patients are shown in Table 1.…”
Section: Literature Search Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Asar 2021 [36] −2.92 −3.78 −2.06 6.68 <.00001 Chen 2021 [38] −2.49 −3.28 −1.71 6.26 <.00001 Ciftci 2020 [29] −2.81 −3.65 −1.98 6.59 <.00001 Ghamry 2019 [21] −2.94 −3.79 −2.09 6.77 <.00001 ESkin 2020 [22] −2.36 −3.09 −1.62 6.29 <.00001 Finnerty 2021 [30] −2.96 −3.80 −2.13 6.95 <.00001 Goel 2021 [35] −2.82 −3.67 −1.98 6.54 <.00001 Jin 2021 [37] −2.93 −3.78 −2.07 6.72 <.00001 Singh 2020 [23] −2.78 −3.61 −1.96 6.59 <.00001 Wahdan 2021 [31] −2.45 −3.16 −1.74 6.79 <.00001 Wang 2021 [26] −2.84 −3.72 −1.97 6.40 <.00001 Yayik 2019 [24] −2.91 −3.76 −2.05 6.67 <.00001 YU 2021 [32] −2.80 −3.64 −1.97 6.57 <.00001 Yörükoğlu 2021 [33] −2.92 −3.77 −2.07 6.73 <.00001 Zhang 2020 [25] −2.70 −3.51 −1.89 6.53 <.00001 Zhang 2021 [34] −2.96 −3.80 −2.13 6.94 <.00001 Zhang JJ 2021 [28] −2.97 −3.80 −2.14 7.03 <.00001 Zhu 2021 [27] −2.93 −3.77 −2.09 6.83 <.00001 CI = confidence interval, SMD = standardized mean differences.…”
Section: Other Outcomesmentioning
confidence: 99%
“…Title and abstract screening eliminated 2,101 citations. Out of the remaining 63 studies, 50 were excluded after full-text review, leaving 13 studies for inclusion (Table 1) (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). All the included studies were RCTs.…”
Section: Selection Of Articles Study Characteristics and Study Qualitymentioning
confidence: 99%